IT/IS Roles as the Business Enabler on PT. Voltras Travel - Trisna Febriana; Ardhianiswari Diah Ekawati; Yunita Kartika Sari (ComTech: Computer, Mathematics and Engineering Applications, 2015)
Technology is very important in facilitating the success of the company to win competition. Organizations strive to select and utilize the various technologies in order to support the achievement of their visions and missions. Development of technology covers all aspect from the hardware, software, data communication of technologies and application. The purpose of this research is to study the development of technologies or trend regarding the usage of the said technology in society. The research method of this research was conducted through direct observation, literature review, evaluation and verification of the resultbefore it was standardized into a usage model of technology. The development of business strategy in this research used SWOT analysis. The study’s result stated that there are five technology trends which are used in today’s society.